590
|
1 extern int printf(const char *,...);
|
|
2
|
|
3 #ifdef INLINE
|
|
4 #else
|
|
5 #define INLINE
|
|
6 #endif
|
|
7
|
|
8 int hoge();
|
|
9 void aho();
|
|
10
|
|
11 int
|
|
12 main()
|
|
13 {
|
|
14 aho();
|
|
15 return hoge();
|
|
16 }
|
|
17
|
|
18 INLINE void
|
|
19 aho()
|
|
20 {
|
|
21 register int i = 0;
|
|
22 register int a0 = 0;
|
|
23 register int a1 = 0;
|
|
24 register int a2 = 0;
|
|
25 register int a3 = 0;
|
|
26 register int a4 = 0;
|
|
27 register int a5 = 0;
|
|
28 register int a6 = 0;
|
|
29 register int a7 = 0;
|
|
30 register int a8 = 0;
|
|
31 register int a9 = 0;
|
|
32 register int aa = 0;
|
|
33 register int ab = 0;
|
|
34 register int ac = 0;
|
|
35 register int ad = 0;
|
|
36 register int ae = 0;
|
|
37
|
|
38 i= i+1;
|
|
39 int j;
|
|
40 j= i+1;
|
|
41 int k=3;
|
|
42 k = j+4;
|
|
43 k = ((((i+1)-((j*(k+3))+2))-((j*3*(2+(2+(2+k))))+k*(2+(2+(2+k))))-((j*4)+k*3)
|
|
44 + ((i+1)-((j*(k+3))+2))-((j*3*(2+(2+(2+k))))+k*(2+(2+(2+k))))-((j*4)+k*3))
|
|
45 + (((i+1)-((j*(k+3))+2))-((j*3*(2+(2+(2+k))))+k*(2+(2+(2+k))))-((j*4)+k*3)
|
|
46 + ((i+1)-((j*(k+3))+2))-((j*3*(2+(2+(2+k))))+k*(2+(2+(2+k))))-((j*4)+k*3)))
|
|
47 + ((((i+1)-((j*(k+3))+2))-((j*3*(2+(2+(2+k))))+k*(2+(2+(2+k))))-((j*4)+k*3)
|
|
48 + ((i+1)-((j*(k+3))+2))-((j*3*(2+(2+(2+k))))+k*(2+(2+(2+k))))-((j*4)+k*3))
|
|
49 + (((i+1)-((j*(k+3))+2))-((j*3*(2+(2+(2+k))))+k*(2+(2+(2+k))))-((j*4)+k*3)
|
|
50 + ((i+1)-((j*(k+3))+2))-((j*3*(2+(2+(2+k))))+k*(2+(2+(2+k))))-((j*4)+k*3)));
|
|
51 printf("%d %d %d\n",i,j,k);
|
|
52 int m=3;
|
|
53 k = ((((i+1)-((j*(k+3))+2))-((j*3*(2+(2+(2+k))))+k*(2+(2+(2+k))))-((j*4)+k*3)
|
|
54 + ((i+1)-((j*(k+3))+2))-((j*3*(2+(2+(2+k))))+k*(2+(2+(2+k))))-((j*4)+k*3))
|
|
55 + (((i+1)-((j*(k+3))+2))-((j*3*(2+(2+(2+k))))+k*(2+(2+(2+k))))-((j*4)+k*3)
|
|
56 + ((i+1)-((m*(k+3))+2))-((j*3*(2+(2+(2+k))))+k*(2+(2+(2+k))))-((j*4)+k*3)))
|
|
57 + ((((i+1)-((j*(k+3))+2))-((j*3*(2+(2+(2+k))))+k*(2+(2+(2+k))))-((j*4)+k*3)
|
|
58 + ((i+1)-((j*(k+3))+2))-((j*3*(2+(2+(2+k))))+k*(2+(2+(2+k))))-((j*4)+k*3))
|
|
59 + (((i+1)-((j*(k+3))+2))-((j*3*(2+(2+(2+k))))+k*(2+(2+(2+k))))-((j*4)+k*3)
|
|
60 + ((i+1)-((j*(k+3))+2))-((j*3*(2+(2+(2+k))))+k*(2+(2+(2+k))))-((j*4)+k*3)));
|
|
61 printf("%d %d %d\n",i,j,k);
|
|
62 }
|
|
63
|
|
64 int
|
|
65 hoge()
|
|
66 {
|
|
67 aho();
|
|
68 return 0;
|
|
69 }
|